Explore the Intention to Learn Body Painting: An Application of Theory of Planned Behavior - WU, LI-AN (Advances in Social Sciences Research Journal, 2022)
This research aims at the relationships between the subjective norm, attitude, personal norm, perceived behavioral control, and behavioral intention. The interviewees consist of the body painting learners, who have undergone the survey of the print questionnaire. After deleting 20 ineffective questionnaires, the remaining 300 questionnaires yield the effective response rate of 93.7%. The conclusions based on this research are listed as follow: (1) The subjective norm places positive impact on the attitude. (2) The intention is positively influenced by the attitude. (3) The subjective norm positively impacts on the personal norm of the intention. (4) The intention is positively influenced by the personal norm. (5) The perceived behavioral control is positively influenced by the subjective norm. (6) The perceived control positively effects on the intention. (7) The subjective norm positively influences the intention. (8) The attitude fully places the mediation effects between the subjective norm and the behavioral intention. (9) The personal norms partially place the mediation effect between the subjective norm and the behavioral intention. (10) The perceived behavioral control partially places the mediation effect between the subjective norm and the behavioral intention.